Nilai Tahanan Kontak Pada PMS BAY Cengkareng Terhadap Rugi Daya Di Gardu Induk Duri Kosambi - Novi Gusti Pahiyanti; Sigit Sukmajati; Abdul Malik (Sekolah Tinggi Teknik - PLN, 2021)
The generator is a source of electrical energy that will be distributed to the substation which will then be channeled back to consumers. The separator is the equipment at the substation which supports the performance of the equipment. Maintenance on the separator should be maintained on a regular basis which consists of cleaning and testing. One of the tests is contact resistance. This test is carried out to determine the resistance value of the Separator contact according to the standard. Power loss is affected by a high resistance value, because the power loss is the square of the current multiplied by the resistance of the contact. This study was conducted to determine the value of contact resistance against power loss by comparing the value of contact resistance in 2020 and 2021. The power loss obtained is relatively small, namely the highest power loss is in the 2021 phase R, which is 6.417 Watt or 0.006417 kW. Meanwhile, the lowest power loss is in phase T in 2020, which is 2.603 Watt or 0.002603 kW. The effect of contact resistance in this study is that if it is found that the contact resistance value exceeds the standard so that a high contact resistance value is obtained, it will be able to cause the equipment to become hot, and when it reaches its melting point, it will be able to melt the separating knife or disconnecting switch, so that the temperature does not change. can be held back by the contact resistance according to its ability, there will be an explosion at the Separator contact which will cause a trip.